TGF-β-induced autophagy in pulmonary artery endothelial cells associated with chronic thromboembolic pulmonary hypertension - Ying-Ju Lai; Yen-Lin Huang; Ching-Yen Tsai; Po-Ru Chen; Chi-Jen Chang; Yung-Hsin Yeh; Celina De Almeida; Hsao-Hsun Hsu (Journal of Molecular Medicine, 2026)

Excellent durability and outstanding performance of forward osmosis membrane containing carbon blacks and carbon nanotubes derived from CO2 - Shao-Tung Chang; Shivam Gupta; Hsin-Chieh Lee; Yi-Ting Lai; Jarrn-Horng Lin; Chi-Young Lee; Nyan-Hwa Tai (Desalination, 2026)

Mangiferin attenuates aflatoxin B1–Induced ferroptosis by activating of Nrf2-Signaling and mitochondrial biogenesis in human ovarian granulosa cells - Chi-Wai Ruan; Hsin-Yi Tsai; Chih-Hsin Hung; Ming-Wei Lin (Food and Chemical Toxicology, 2026)

Weather source heterogeneity affects disease forecasting: A case study of rice bacterial leaf blight in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Yea-Fang Wu; Chi-Yu Chen; Guan-Ying Huang; Hau-Ping Chou; Chien-Chih Kuo; Hsin-Yuh Wu; Qiao-Juan Lai; Chih-Wei Wang; Yi-Chen Tsai; Chang-Hsin Kuo; et al. (Agricultural and Forest Meteorology, 2026)

FBG-based dynamic characterization of a scaled offshore wind turbine foundation model under impact and recorded seismic excitations - Jui-Chi Lin; Yi-Lun Liao; Bor-Yann Chen; I-Hsin Chiu; Wan-Yu Xu; You-Chen Liao; Yi-Heng Yang; Yu-Hsi Huang (Ocean Engineering, 2026)

Piezo-photocatalysis with BaTiO3 nanorod arrays–Ag nanoparticle composites for the photodegradation of rhodamine B - Yen-Lun Chiu; Thi Nghi Nhan Nguyen; Hsin-Yu Chi; Heng-Jun Lin; Kao-Shuo Chang (Journal of Environmental Chemical Engineering, 2026)

Levels and emission factors of polycyclic aromatic hydrocarbons in night market cooking fumes - Thi-Hieu Le; Cindy Soo Yun Tan; Hsin-Chieh Kung; Riza P. Gumaling; Danielle E. Que; How-Ran Chao; Ying I. Tsai; Xuan-Thanh Bui; Guo-Ping Chang-Chien; Lin-Chi Wang (Atmospheric Environment, 2026)

Monitoring photochemical reactions catalyzed by nano-titanium dioxide using electrospray laser desorption ionization mass spectrometry - Min-Zong Huang; Hsin-Hui Liang; Chi-Yang Lee; Shu-Yao Lin; Chun-Mei Wu; Jentaie Shiea (Analytica Chimica Acta, 2026)

Effective metal recovery from lithium-ion battery waste using a ternary deep eutectic solvent in a high solid-to-liquid ratio under mild and ambient conditions - Hsin-Jou Cheng; Yi-Jane Lin; Shu-Chi Chang; Shih-Yen Yang; Ting-Wei Lee; Chiaying Chen (Journal of Environmental Chemical Engineering, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Population structure of Tachypleus tridentatus in Xiamen Bay: Proposing a network of transboundary marine protected areas - Yi-Hua Jin; Yi-Jia Shih; Hsin-I. Lin; Ya-Hui Chen; Yung-Sheng Cheng; Chia-Fa Lee; Yang-Chi Chang; Yi Chang (Regional Studies in Marine Science, 2025)

Entropy-stabilized multi-element 2D TMDs: Tunable electronics and enhanced thermal stability - Ching-Wei Chin; Chong-Chi Chi; Kai-Yuan Hsiao; Yi-Hsin Fang; Dun-Jie Jhan; Chun-Hui Lin; Ming-Pei Lu; Ming-Yen Lu (Chemical Engineering Journal, 2025)

A novel approach for quantifying therapeutic monoclonal antibodies in blood through liquid chromatography–tandem mass spectrometry - Tsun-Hao Chi; Chiao Lo; Shin-Yi Lin; Yi-Hsin Liang; Wen-Chi Chang; Chia-Yu Yeh; Huai-Hsuan Chiu; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Effect of tertiary amine carbon quantum dots incorporation on oil/water separation performance of membranes - Gabriel V. Carballo; Hsin-Yi Lin; Pei-Chen Chen; Hong-Li Yang; Rhoda B. Leron; Chi-Lan Li; Hui-An Tsai; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

What does it mean when the pleasant smells come and go? Correlation between UPSIT odor identification status and fluctuation of non-motor symptoms in Parkinson’s disease - Hsin-Bei Lei; Ting-Chun Fang; Yu-Hsuan Lin; Shih-Chi Chiu; Ming-Hong Chang; Yi-Jen Guo (Acta Neurologica Belgica, 2025)
Parkinson’s disease (PD) is characterized by motor and non-motor symptoms, including olfactory dysfunction. Prior studies have shown that olfaction deteriorates with disease progression, however fluctuations in olfaction and related PD symptoms have been less explored. This study aimed to investigate correlations between changes in odor identification ability and PD symptoms. PD patients recruited from Taichung Veterans General Hospital underwent at least two consecutive Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) and University of Pennsylvania Smell Identification Test (UPSIT) evaluations. The patients were grouped based on changes in olfactory identification ability between evaluations, and fluctuations in PD symptoms were compared between groups. Ninety-seven PD patients with 114 complete sets of data were analyzed. Significant divergent results were observed between changes in five MDS-UPDRS non-motor subscores and the conversion status of five pleasant odors, including anxiety vs. bubble gum, apathy vs. banana, dizziness vs. coconut, urination vs. root beer, and dopamine dysregulation syndrome (DDS) vs. grape. Fluctuations in the ability to detect pleasant odors, may have a complex interaction with other non-motor symptoms, including in the neurobehavioral and autonomic domains. Serial monitoring of olfactory function, particularly with pleasant odors, may provide valuable insights for tracking non-motor symptoms in PD and warrants further investigation into their therapeutic implications.

Versatile g-C3N4/AlOOH nanocomposites: Efficient photocatalyst for dye removal, algae inactivation, and glucose detection - Hsiu-Cheng Chen; Ting-Yu Lin; Hsin-Cheng Peng; Yu-Hsuan Lee; Ruey-Chi Wang (Chemosphere, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Long-term subculture induces syncytialization and influent the response to bisphenol A (BPA) of placental JEG-3 cells - Yu-Shiuan Huang; Ai-An Chang; Zhi-Jie Yang; Jung-An Chen; Chi-Kang Lin; Hsin-Chieh Lan (Reproductive Toxicology, 2024)

Investigating illicit drug hotspots and daily variations using sewer-network wastewater analysis - Hank Hui-Hsiang Lin; Ming-Chi Hsieh; Jennifer Ia Wen Wen Liu; Yu-Hsiang Wang; Shu-Jie Huang; En Lien; Li-Wei Huang; Pei-Te Chiueh; Hsin-Hsin Tung; Angela Yu-Chen Lin (Chemosphere, 2024)

Evaluating the embryotoxicity of benzophenone-based photoinitiators in stem cells and zebrafish embryos - Chen-Yi Weng; Tzu-Ching Chang; Jun-Yang Liou; Ju-Hsin Hsu; Chia-Chi Ho; Salim Arrokhman; Pinpin Lin (Toxicology, 2024)

Effects of physical sterilization on microbial safety, nutritional composition, and antioxidant activity of queen bee larva powder, a by-product of royal jelly production - Yu-Hsin Chen; Jer-An Lin; Chi-Chung Peng; Pei-Shou Hsu; Tzu-Hsien Wu; Yen-Hou Chen; Ming-Cheng Wu (Food Control, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Identification of organic constituents on atmospheric particulate matter in the East Asian background air of free troposphere by GC×GC-TOFMS - Chang-Feng Ou-Yang; Yi-Jun Chen; Hsin-Cheng Hsieh; Chung-Te Lee; Kai-Hsien Chi; Neng-Huei Lin; Chih-Chung Chang; Jia-Lin Wang (Chemosphere, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Deciphering microbial communities and their unique metabolic repertoire across rock-soil–plant continuum in the Dayoukeng fumarolic geothermal field of the Tatun Volcano Group - Jung-Sheng Chen; Bashir Hussain; Hsin-Chi Tsai; Viji Nagarajan; Rajendran Senthil Kumar; I-Ching Lin; Bing-Mu Hsu (Environmental Science and Pollution Research, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Extreme seismic anisotropy indicates shallow accumulation of magmatic sills beneath Yellowstone caldera - Sin-Mei Wu; Hsin-Hua Huang; Fan-Chi Lin; Jamie Farrell; Brandon Schmandt (Earth and Planetary Science Letters, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

The thermal degradation and soil recovery of thermal treatment of field-weathered decabrominated diphenyl ether-contaminated soil - Jennifer Ia Wen Wen Liu; Yu-Jie Lin; Chi-Fong Ko; Jiann-yuan Ding; Yang-hsin Shih (Chemosphere, 2023)

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

An ensemble learning based hybrid model and framework for air pollution forecasting - Yue-Shan Chang; Satheesh Abimannan; Hsin-Ta Chiao; Chi-Yeh Lin; Yo-Ping Huang (Environmental Science and Pollution Research, 2020)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Benefit analysis of flood adaptation under climate change scenario - Hsin-Chi Li; Shih-Yun Kuo; Wei-Bo Chen; Lee-yaw Lin (Natural Hazards, 2019)

Analysis of the Aso-Bridge landslide during the 2016 Kumamoto earthquakes in Japan - Ching Hung; Guan-Wei Lin; Huei-Sian Syu; Chi-Wen Chen; Hsin-Yi Yen (Bulletin of Engineering Geology and the Environment, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Tropical SST forcing on the anomalous WNP subtropical high during July–August 2010 and the record-high SST in the tropical Atlantic - Chi-Cherng Hong; Ming-Ying Lee; Huang-Hsiung Hsu; Nai-Hsin Lin; Ben-Jei Tsuang (Climate Dynamics, 2015)

Benzodiazepine therapy in psychiatric outpatients is associated with deliberate self-poisoning events at emergency departments—a population-based nested case–control study - Hsin-I Shih; Ming-Chia Lin; Che-Chen Lin; Hsiang-Chin Hsu; Hsin-Ling Lee; Chih-Hsien Chi; Fung-Chang Sung; Yen-Jung Chang; Chia-Hung Kao (Psychopharmacology, 2013)

Cell Hypertrophy and MEK/ERK Phosphorylation are Regulated by Glyceraldehyde-Derived AGEs in Cardiomyocyte H9c2 Cells - Shun-Yao Ko; I-Hsuan Lin; Tzong-Ming Shieh; Hsin-An Ko; Hong-I Chen; Tzong-Cherng Chi; Shu-Shing Chang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2013)

Oyster shell reduces PAHs and particulate matter from incense burning - Chi-Ru Yang; Tzu-Hsing Ko; Yuan-Chung Lin; Suen-Zone Lee; Yih-Feng Chang; Hsin-Ta Hsueh (Environmental Chemistry Letters, 2013)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Alternative splicing and genetic diversity of the white collar-1 (wc-1) gene in cereal Phaeosphaeria pathogens - Ericka Yen-Hsin Chiu; Ying-Hong Lin; Wei Wu; Qijian Song; Pi-Fang Linda Chang; Ling-Yan Gao; Chun-Chi Chou; Peter P. Ueng (European Journal of Plant Pathology, 2010)

Simultaneous analysis of nine components in patch preparations of Ru-Yi-Jin-Huang-San by high-performance liquid chromatography - Horng-Liang Lay; Chia-Chi Chen; Shiow-Chyn Huang; Thau-Ming Cham; Tian-Shung Wu; I-Hsin Lin (Journal of Natural Medicines, 2010)

Role of the DxxDxD motif in the assembly and stability of betanodavirus particles - Yi-Min Wu; Chi-Hsin Hsu; Chun-Hsiung Wang; Wangta Liu; Wei-hau Chang; Chan-Shing Lin (Archives of Virology, 2008)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Isolation and characterization of two novel colon cancer cell lines from Chinese patients - Dan-Ning Hu; Shiaw-Min Hwang; Xi-Zhang Lin; Pei-Yuh Yang; Chi-Hong Tsai; Qiang Huang; Hsin-Yi Huang; Min-Huo Hwang (In Vitro Cellular & Developmental Biology - Animal, 2007)

Soil Lead Immobilization Using Phosphate Rock - Chi-Wen Lin; Jonny Lian; Hsin-Hsiung Fang (Water, Air, & Soil Pollution, 2005)

Anti-hepatitis B surface antigen IgG1 subclass is predominant in individuals who have recovered from hepatitis B virus infection, chronic carriers and vaccinees - Lina Wang; Shyh-Jye Lin; Ju-Hsin Tsai; Chung-Hung Tsai; Chung-Chuan Tsai; Chi-Chiang Yang (Medical Microbiology and Immunology, 2005)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)